Implementasi Lelang Barang Jaminan Pada Pt. Bank Muamalat Indonesia Tbk. Kantor Cabang Panyabungan - Windari Windari; Novi Novi (AGHNIYA : Jurnal Ekonomi Islam, 2021)
PT. Bank Muamalat Indonesia Tbk. The PANYABUNGAN Branch Office is a part of a Sharia Commercial Bank. One of the products offered by the bank is financing. Distribution of financing to PT. Bank Muamalat Indonesia Tbk. The Panyabungan Branch Office must comply with the principles of prudence and coverage of risks due to default. This research is motivated because the customer cannot pay off the financing provided by the bank so that the bank executes and auction off the customer's collateral. After the collateral is executed, the bank will hand it over to KPKNL for auction according to the limit price set by the bank. So the formulation of the problem in this research is how the auction of collateral at PT. Bank Muamalat Indonesia Tbk. Panyabungan Branch Office. With the aim of knowing the auction process of collateral at PT. Bank Muamalat Indonesia Tbk. Panyabungan Branch Office. The method used in this research is a qualitative research method with a descriptive approach. The data collection techniques used were observation, interview and documentation. Based on the results of the research conducted, the researcher can conclude that if the customer does not pay off his debt at a predetermined time, the collateral will be auctioned off. Previouslythe bank gave warning letters three times and provided relief tocustomers to sell the collateral themselves. And if within threemonths the customer was still unable to sell the collateral, the bankwould submit an auction to the KPKNL in the city of Panyabungan, because the auction is the last step that must be taken by the bankin order to return the funds that have been issued by the bank tocustomers who commit default.